2016
DOI: 10.1101/083980
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transposable element exaptation is the primary source of novelty in the primate gene regulatory landscape

Abstract: 16Gene regulation plays a critical role in the evolution of phenotypic diversity. We investigated 17 the evolution of liver promoters and enhancers in six primate species. We performed ChIP-18 seq for two histone modifications and RNA-seq to profile cis-regulatory element (CRE) 19 activity and gene expression. The primate regulatory landscape is largely conserved across 20 the lineage. Conserved CRE function is associated with sequence conservation, proximity 21 to coding genes, cell type specificity of CRE… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 126 publications
(4 reference statements)
0
10
0
Order By: Relevance
“…In this paper, we demonstrate that, even though TEs play important roles in remodeling regulatory networks and enabling functional innovation (Lynch et al 2011(Lynch et al , 2015Chuong 2013;Chuong et al 2016a;Trizzino et al 2016), they are depleted for regulatory activity compared with their prevalence across the human and mouse genomes. This should not be…”
Section: Discussionmentioning
confidence: 87%
“…In this paper, we demonstrate that, even though TEs play important roles in remodeling regulatory networks and enabling functional innovation (Lynch et al 2011(Lynch et al , 2015Chuong 2013;Chuong et al 2016a;Trizzino et al 2016), they are depleted for regulatory activity compared with their prevalence across the human and mouse genomes. This should not be…”
Section: Discussionmentioning
confidence: 87%
“…Contributions of TEs to regulatory landscapes are particularly pronounced when species-specific enhancers are considered, including through waves of repeat expansions [12]. For example, the majority of ape-specific and human-specific liver enhancers overlap TEs (77% of ape-specific enhancers compared with 16% of evolutionarily conserved enhancers) [50]. Quantitative comparisons of enhancer landscapes between chimpanzee and human cranial neural crest cells (CNCCs) showed that speciesspecific changes in enhancer activity can be explained by the underlying regulatory sequence divergence and is linked to expression differences in genes involved in development of craniofacial structures [51].…”
Section: Transposable Elements As a Substrate For Evolving New Enhancersmentioning
confidence: 99%
“…A growing body of evidence suggests that specific TE subfamilies have been coopted for transcriptional regulation in a number of biological contexts (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). In particular, TEassociated enhancers contributed to the evolution of early development (17), placentation (18), mammalian pregnancy (14),…”
mentioning
confidence: 99%